PENGARUH IFR TERHADAP COE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Purwanti, Sri; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test empirically the influence of Internet Financial Reporting (IFR) which consists of IFR index content, IFR index timelines, and IFR index presentation to the Cost of Equity Capital (COE) on the companies which are listed in Indonesia Stock Exchange.This research is a qualitative research. The population is all manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2011 periods. The sample collection technique has been done by using purposive sampling method. The samples are 94 manufacturing companies. The data analysis method has been done by using multiple linear regression analysis. Based on the result of the data analysis and hypothesis test, it can be concluded that IFR variable, index content dan index timeliness has negative and significant influence to the COE on manufacturing companies which are listed in Indonesia Stock Exchange. Meanwhile, index presentation has positive and significant influence to the COE on manufacturing companies which are listed in Indonesia Stock Exchange.Keywords: IFR, Index Content, Index Timeliness, Index Presentation, COE